Overview of scientific papers on subject analysis - Figueiredo, Nathaniel Reis de; Gonçalves, Thaísa Antunes (AtoZ: novas práticas em informação e conhecimento, 2025)
Introduction: subject analysis is a topic that belongs to reflections on document indexing. It is related to the extraction of concepts from a document that represents its content for later recovery in an information retrieval system. Reflections on this activity, however, are marked by terminological differences that mirror theoretical differences. Based on this, we sought to question how the concept is approached in the Brazilian scientific field of Librarianship and Information Science. Method: using the Proknow-C data collection instrument, the search focused on the objective of building a bibliographic portfolio of scientific papers in Portuguese retrieved from the Base de Dados em Ciência da Informação (BRAPCI) from terms related to the subject. Results: it can be seen that the papers with the greatest scientific relevance are from bibliographic research, focused on theoretical issues, and that there are few reflections on the peculiarities of analysis of each document typology, especially those that differ from records based on written texts, such as iconographic, three-dimensional, musical or audiovisual documents. Conclusions: This portfolio served to recognize scientific papers, authors, journals and relevant keywords on the subject, in addition to enabling the diagnosis of the main theoretical trends on subject analysis in Brazil, and, mainly, to indicate paths for future research that may be scientifically significant for this field of knowledge.